(untitled) (Journal of Economic Research & Business Administration, 2016)
Tax deductions are an important instrument in the tax adjusting and administration. Tax deductions are called to carry out a stimulant and so cial function. In the economy of country by means of tax deductions affect activity of managing subjects, creating favourable business climate. Tax deductions create certain advantages and for the separate categories of population, businessmen. Tax deductions create certain advantages and for the separate categories of population, businessmen. Tax deductions corresponding to the certain tax have certain lines, signs and forms, dis tinguishing them from other instruments of the tax adjusting. This article examines the impact of tax incentives on economic activity in the Republic of Kazakhstan. We study the problem of tax incentives through tax breaks.